Kaji Eksperimental Torsi Statik Dan Torsi Dinamik Turbin Hidrokinetik Savonius Type Bach Tiga Sudu Dua Tingkat - Agung Sitompul; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Throughout human history major advances in culture have always been followed by increasing energy consumption. Hydrokinetic energy can be used in savonius turbines, with the density of water greater than the density of air, the Savonius hydrokinetic turbine can extract sufficient kinetic energy even at low water flow rates. The purpose of this study is to determine the static torque and dynamic torque generated from the two-level savonius turbines type bach. The hydrokinetic turbines were studied three stages savonius type of bach turbines with varying first and second levels (15 cm: 15 cm; 17 cm: 13 cm; and 20 cm: 10 cm) at the same of total turbines height. The aspect ratio of dimensions were 1.1, 0.2 of overlap ratio, rotor height of (H) 0.3 m, rotor diameter of (D) 0.33 m, turbine diameter of (d) 0.3 m, and with variations in water flow velocity of ( V) 0.3 m / s and 0.65 m / s in the water tunnel. Both of these torsions were obtained in stationary conditions (static torque) for each azimuth angle and moving conditions (dynamic torque) of no load and until they stop rotating by utilizing the braking force on a pulley with variations in loading. Based on the data obtained, the results of bach savonius type turbine research produce the largest dynamic torque of 0.42 Nm and static torque of 0. 528 Nm in variations of 15 cm: 15 cm.Keywords : Savonius Turbine, Static Torque, Dynamic Torque